2004
DOI: 10.7863/jum.2004.23.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Second-Trimester Sonography and Trisomy 18

Abstract: Objective. To estimate the risk of trisomy 18 with the finding of isolated choroid plexus cysts after a standard sonographic examination that is extended to include the fetal hands. Methods. A retrospective chart review was performed on all fetuses with choroid plexus cysts on second-trimester sonographic examinations. When choroid plexus cysts were identified, our standard protocol for fetal evaluation was expanded to include the hands. If no other findings were noted on completion of this examination, the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Our study showed 32% of trisomy 18 cases had cerebellar hypoplasia by brain ultrasonography. By the prenatal sonography, Bronsteen et al [2004] and Sahinoglu et al [2004] both found that larger choroid plexus cysts were associated with trisomy 18. Our study revealed that 19% of our cases showed choroid plexus cysts.…”
Section: Structural Defectsmentioning
confidence: 99%
“…Our study showed 32% of trisomy 18 cases had cerebellar hypoplasia by brain ultrasonography. By the prenatal sonography, Bronsteen et al [2004] and Sahinoglu et al [2004] both found that larger choroid plexus cysts were associated with trisomy 18. Our study revealed that 19% of our cases showed choroid plexus cysts.…”
Section: Structural Defectsmentioning
confidence: 99%
“…As malformaçÔes das extremidades inferiores e dos pĂ©s jĂĄ foram encontradas em quase dois terços dos fetos com trissomia 18 19 . No geral, as malformaçÔes mais comumente descritas em fetos com trissomia do cromossomo 18 envolvem cĂ©rebro, coração e membros 20 . Em decorrĂȘncia destas malformaçÔes, Ă© bastante comum o achado de crescimento intrauterino restrito 13 .…”
Section: Discussionunclassified
“…In the medical literature, the frequency of structural abnormalities in fetuses with T13/18 is high, and is found in 80 to 100%. 26,32,47,[54][55][56] In this study, of the 9 fetuses with prenatal diagnosis of T13/18 that showed no MF at the time of the karyotype studies, 6 underwent karyotype studies using CVS in the first trimester, showing an increased NT as an indication.…”
Section: Discussionmentioning
confidence: 99%